ORIENTALIS DAN PERANANNYA DALAM MEMPELAJARI BAHASA ARAB - Agustiar Agustiar (POTENSIA: Jurnal Kependidikan Islam, 2015)
Orientalisme is a knowledge about easterners which is important to we know. Because beside positive values consisting in it also there are negative values. That negative values represent noxious poison in effort paralyse Islam with understanding able to be groggy of clan belief in God of muslimin to al-Qur'an, Rasul, apocalypse and others. Clan of orientalis in general consist of people of Nasrani and Jew having hand in glove with Christian missionary mission and also colonist. They investigate and collect science coming eastward with various target and motiv which they wish. Even among all orientalis in its importance study Arab language there is with aim to be negative that is for the destroy of association of Islam, but there is also with aim to be positive that is devoted x'self solely for science by bearing its masterpieces in Arab language area and its literature. A lot of easting books written by clan of orientalis particularly about Islam concerning with problem of Alqur'an, Al-Hadist, Tarekh and Culture of Islam, Islam law and others. To investigate science above, Arab language is as especial bridge for them. The language of Arab which in advance they study to disclose the sciences to Europe language like Latin language, English, French, Germany , Dutch and others. Their ability study Arab language, making they ready to translate into their language and also write books in Arab language.